Implementation of Imam Al-Ghazali's Production Principles In The Halal Industry (Study on Tempe/Tahu Factory in Tanete Riattang District, Bone Regency) - Sulfajri; Andi Patimbangi; Muh. Arafah (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2025)
This study aims to analyze the application of Imam Al-Ghazali's production principles in the halal industry, especially in tempeh and tofu factories in Tanete Riattang District, Bone Regency. The research method used is qualitative with an exploratory approach through observation, interviews, and documentation. The results showed that Imam Al-Ghazali's production principles, such as good intentions, justice in production, worldly and afterlife balance, prohibition of usury and speculation, and social responsibility have been applied by business actors. They are committed to providing quality halal products, maintaining worker welfare, avoiding usury practices, and contributing to the surrounding community. However, challenges are still found in terms of Islamic economic literacy and access to halal raw materials. By understanding and optimizing Islamic production principles, the halal industry can develop sustainably, creating economic and spiritual balance in business. This study is expected to be a reference for business actors in applying Islamic values in the halal industry Key Words:Halal industry, Islamic Production, Imam Al-Ghazali, Tempe/Keto factory